Pengembangan Usaha Mikro Kerajinan Bokor Berbasis Budaya dan Ekonomi Guna Mendukung Keberlanjutan Ekonomi Lokal Di Desa Bresela - I Gusti Agung Ayu Pramita Indraswari; Ni Putu Budiadnyani; Putu Pande R. Aprilyani Dewi; I G. A. N Alit Sumantri (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
This study aims to examine and develop the potential of micro-enterprises producing traditional Balinese bokor crafts in Bresela Village as an effort to preserve culture while strengthening the local economy. Bokor, as one of Bali's traditional crafts rich in cultural value, holds significant economic potential if managed strategically and sustainably. Using a descriptive qualitative approach, data was collected through observation, interviews with local artisans, and documentary studies. The research findings indicate that the development of culture-based bokor micro-enterprises can strengthen local identity, increase community income, and create job opportunities aligned with local wisdom. Support for training, design innovation, and digital marketing also play crucial roles in the success of this enterprise development. With the right strategy, the bokor craft business can become one of the pillars of a sustainable local economy amid the tide of modernization and globalization.